Clinical Trials of Cannabidiol for Substance Use Disorders: Outcome Measures, Surrogate Endpoints, and Biomarkers - Morel, Alix; Lebard, Pierre; Dereux, Alexandra; Azuar, Julien; Questel, Frank; Bellivier, Frank; Marie-Claire, Cynthia; Fatséas, Mélina; Vorspan, Florence; Bloch, Vanessa (Frontiers in Psychiatry, 2021)
Background: Cannabidiol (CBD) is a cannabinoid of potential interest for substance use disorders treatment. Our aim was to review the outcome measures, surrogate endpoints and biomarkers in published and ongoing randomized clinical trials. Methods: We conducted a search in PubMed, Web of science, PMC, Psychinfo, EMBASE, CENTRAL Cochrane Library, “clinicaltrials.gov”, “clinicaltrialsregister.eu” and “anzctr.org.au” for published and ongoing studies. Inclusion criteria were randomized clinical trials (RCT) examining the use of CBD alone or in association, in all substance use disorders. Included studies were analyzed in detail and their qualities assessed by a standardized tool (CONSORT 2010). A short description of excluded studies, when consisting in controlled short term or single administration in non-seeking treatment drug users, is provided. Findings: The screening retrieved 207 published studies, including only 3 RCT in cannabis use disorder. Furthermore, 12 excluded studies in cannabis, tobacco and opioid use disorders are described. Interpretation: Primary outcome were validated withdrawal symptoms scales and drug use reduction in the 3 RCT. In the short-term or cross-over studies, the outcome measures were visual analogue scales for subjective states, self-rated scales for withdrawal, craving, anxiety or psychomimetic symptoms, as well as laboratory tasks of drug-induced craving, effort expenditure, attentional bias for the substance, impulsivity, or anxiety to serve as surrogate endpoints for treatment efficacy. Of note, ongoing studies are now adding peripheral biomarkers of the endocannabinoid system status to predict treatment response. Conclusion: The outcome measures and biomarkers assessed in the ongoing CBD trials for substance use disorders are improving.